Summary catalogue of the cultural valuables stolen and lost during the second world war = . Svodnyj Katalog kul'turnych cennostej, pochiščennych i utračennych v period vtoroj mirovoj vojny (Ministry of Culture of the Russian Federation, 1999)
Volume 2 in Russian. 1,1: The Tsarskoye Selo State Museum Zone: The Catherine Palace.